Clinical study of isosorbide mononitrate treatment for angina pectoris in coronary heart disease - TAN, ZHENG (D.A. Spandidos, 2013)
The aim of this study was to observe and investigate the clinical efficacy of an intravenous drip of isosorbide mononitrate (ISMN) for the treatment of angina pectoris in coronary heart disease. A total of 102 patients with angina pectoris in coronary heart disease were divided into two groups. For the treatment group (n=51), 20 mg ISMN was added to 250 ml 0.9% normal saline and administered by intravenous drip for 14 consecutive days, twice daily. For the control group (n=51), 10 mg glyceryl trinitrate was added to 250 ml 0.9% normal saline and administered by intravenous drip for 14 consecutive days, twice daily. The clinical efficacy and adverse reactions were compared between the two groups. The disease symptoms of the two groups were improved. Compared with the control group, the clinical efficacy and electrocardiogram examination results of the treatment group were significantly improved (P<0.05). The intravenous formulation of ISMN is an effective treatment for angina pectoris in coronary heart disease and it has the advantages of fewer adverse reactions and higher safety.